Dynamic failure analysis of static seals under pressure fluctuation in an ultrahigh-pressure water piston pump. (April 2022) - Cheng, Qian; Liu, Yinshui; Wang, Zhenyao; Wu, Defa; Ma, Yunxiang
For ultrahigh-pressure piston pumps, in the reciprocating action of the piston, the fretting between the static face seal and the mating surface occurs with the change of the pressure in the piston chamber. This phenomenon will seriously affect the service life of the seal ring and lead to the failure of the pump. However, the failure of static seals used to seal ultrahigh-pressures is usually studied from the directions of shear, stress, or rubber material. These studies cannot explain the failure phenomenon of the sealing ring found in our experiment. This paper analyzed the failure of the face seal ring in a piston pump with a maximum pressure of 120 MPa. A two-dimensional axisymmetric finite element model was established based on the Mooney-Rivlin constitutive relation of the rubber material, and the fretting conditions of the sealing ring were analyzed. Combined with the wear scars observed by the scanning electron microscope the face seal ring's dynamic failure mechanism on the ultrahigh-pressure piston pump was determined. A better sealing scheme was proposed and verified by the duration test of the pump, which provided a basis for the design of the sealing of the ultrahigh-pressure fluid with high-frequency fluctuations.